The Legacy of U.S. Educational Leadership: Notes on Distribution and Economic Growth in the 20th Century - Goldin, Claudia; Katz, Lawrence F (American Economic Review, 2001)
The Legacy of U.S. Educational Leadership: Notes on Distribution and Economic Growth in the 20th Century by Claudia Goldin and Lawrence F. Katz. Published in volume 91, issue 2, pages 18-23 of American Economic Review, May 2001